2006
DOI: 10.1007/s10546-006-9099-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface heating in relation to air temperature, wind and turbulence in an urban street canyon

Abstract: Wind and temperature measurements from within and above a deep urban canyon (height/width = 2.1) were used to examine the thermal structure of air within the canyon, exchange of heat with the overlying atmosphere, and the possible impacts of surface heating on within-canyon air flow. Measurements were made over a range of seasons and primarily analysed for sunny days. This allowed the study of temperature differences between opposing canyon walls and between wall and air of more than 15 • C in summer. The wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 35 publications
7
70
0
4
Order By: Relevance
“…These patterns include temperature differences between urban canyons and open spaces (as large squares or parks) [23] and also horizontal and vertical variations inside urban canyons [24]. Such a simplification is often necessary because of the huge amount of ground measurements that would be required to model all of these complex effects.…”
Section: Resultsmentioning
confidence: 99%
“…These patterns include temperature differences between urban canyons and open spaces (as large squares or parks) [23] and also horizontal and vertical variations inside urban canyons [24]. Such a simplification is often necessary because of the huge amount of ground measurements that would be required to model all of these complex effects.…”
Section: Resultsmentioning
confidence: 99%
“…However, several experiments have shown that alone the H/W ratio or the sky view factor, are inadequate to represent the complex thermal phenomena in the urban canyons (ELIASSON, 1996;ELIASSON and HOLMER, 1990;NIAC-HOU et al, 2008a, c). During the night period, convective phenomena related to advection from the surrounding areas or small scale thermal flows because of the heat released by the canyon surfaces, may create unstable conditions in urban canyons (NIACHOU et al, 2008a, c;OFFERLE et al, 2007;CHRISTEN and VOGT, 2004;GRIMMOND et al, 2004;SALMOND et al, 2005;OFFERLE et al, 2006;SINI et al, 1996;KOVAR-PANSKUS et al, 2002). Especially in deep urban canyons with aspect ratios higher than two (H/W [ 2), the possible lack of coupling between the undisturbed air flow above the buildings and the flow in the urban canyon, in combination with the existence of local air flow phenomena, like the development of double air flow vortices or upward and downward thermal flows along the canyon facades, requires a more detailed examination of the thermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in another set of field studies by Georgakis and Santamouris (2006) on a deep canyon of aspect ratio 3.3, it was observed that for approach wind speeds less than 5 ms −1 the air flow patterns were dominated by thermal phenomena and intermittent vortices at the building corners. They found higher temperature above the canyon when compared to canyon temperature and the maximum difference was found to be around 5 • C. However, within the canyon no temperature stratification with height was found and this was also observed by Offerle et al (2007) in a street canyon of aspect ratio 2.1. They deduced that this could be due to the primary vortex in the canyon, driven by the strong shear layer at the canyon top, leading to relatively thorough mixing throughout the canyon.…”
Section: Introductionmentioning
confidence: 92%